2022
DOI: 10.1016/j.ejim.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in clinical presentation and risk stratification in the Emergency Department: An observational multicenter cohort study

Abstract: The aim of this study was to investigate whether sex differences exist in disease presentations, disease severity and (case-mix adjusted) outcomes in the Emergency Department (ED). Methods: Observational multicenter cohort study using the Netherlands Emergency Department Evaluation Database (NEED), including patients ≥ 18 years of three Dutch EDs. Multivariable logistic regression was used to study the associations between sex and outcome measures in-hospital mortality and Intensive Care Unit/Medium Care Unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Our findings indicate that, although there were disease‐specific variations, following an ED visit with any CVD encounter, women were less likely to be hospitalized or to die (ED and overall), even after adjustment for baseline demographic and clinical variables. Consistently, in a study comparing risk stratification of 148 825 men and women in the ED, Candel et al 12 report higher risk of adverse outcomes for men across all triage categories and for almost all presenting complaints. Although this may indicate true higher risk of adverse outcomes in men, there may be several explanations for the observations in our study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our findings indicate that, although there were disease‐specific variations, following an ED visit with any CVD encounter, women were less likely to be hospitalized or to die (ED and overall), even after adjustment for baseline demographic and clinical variables. Consistently, in a study comparing risk stratification of 148 825 men and women in the ED, Candel et al 12 report higher risk of adverse outcomes for men across all triage categories and for almost all presenting complaints. Although this may indicate true higher risk of adverse outcomes in men, there may be several explanations for the observations in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Existing work indicates sex differences in risk stratification and in the manifestation of symptoms in ED presentations. 12 , 13 , 14 Several others have identified, more specifically, sex differences in presentation, management, and outcomes of patients presenting with chest pain or suspected acute coronary syndrome (ACS). 15 , 16 , 17 , 18 However, there are limited data comparing the distribution and outcomes from a wider range of CVD ED presentations in men and women.…”
mentioning
confidence: 99%
“…Sex differences in the prognostic accuracy of scoring systems can often be observed [ 19 ]. This might be attributable to the lower prevalence of female patients in studies involving patients with ACS and that while initially presenting similarly in the ER, women and men do have different outcomes [ 19 , 20 ]. In the present study, when comparing the prognostic performance of the FACTOR score on the all-cause mortality between males and females, it was found that the FACTOR score exhibited similar diagnostic accuracy in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The physiologic variables used in NEWS meet all these requirements (11,12). In addition, age and sex exhibit the same qualities and are predictors for in-hospital mortality (10,13). Other variables have been proposed to use in EWSs, such as biomarkers or frailty measures (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…NEWS assigns 0 to 3 points for all vital signs implying that all vital signs have similar predictive value, which has been shown to be unfounded ( 11 , 12 ). Furthermore, important risk differences exist between men and women at arrival to the ED ( 13 , 14 ). Nonetheless, most studies do not test the performance of EWSs at older age or include sex differences ( 1 , 15 ).…”
mentioning
confidence: 99%